CLASSROOM INTERACTION PATTERNS AND TEACHERS-STUDENTS PERCEPTIONS ON ENGLISH CLASSES AT SMAN 2 BUKITTINGGI WEST SUMATRA - Mike Nurmalia Sari (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2018)
This article aims to describe the results of research on interaction patterns and characteristics of classroom interaction in teaching and learning activities in English class in Bukittinggi West Sumatera, as well as perceptions of students and teachers to the interaction. This research type is descriptive and research data is classroom discourse between teacher and student when studying English, as well as questionnaire of student and teacher to class interaction. Participants are 4 English teachers with 3 meetings for each teacher (12 meetings). The research used classification theory of class interaction type from Lindgren (1981), Wajnryb (1992), and El-Hanafi (2013), while for interaction characteristics used Flanders' Interaction Analysis Code (FIAC) model. The results of this study indicate that the dominant interaction pattern is teacher-student with one way traffic interaction, while the dominant interaction characteristic is the cross content. From teacher perception, dominant interaction pattern is student-student interaction and dominant interaction characteristic is teacher support. Whereas from student perception, dominant interaction pattern is teacher-student with two-way traffic interaction, and characteristic of dominant interaction is content cross. It can be concluded that the interaction pattern and the interaction characteristics that occur in the teaching and learning process are strongly influenced by the material and skills taught by the teacher